Analysis of multi-user video games in teacher training - (:unkn) unknown (ELSEVIER SCIENCE BV, 2010)
Purpose of this study is to examine video games and to analyze common practices, game purposes, contents and features of these games in general terms. Today, video games have become the most attractive and entertaining technology environment particularly for children. Most of the children prefer video games as an entertaining spare time activity. In spite of these features of video games, many studies have been carried out about game based learning environment in literature. These studies are mostly focusing on how these video games are adapted and integrated to learning environment in their most efficient and suitable forms by means of video games. (C) 2010 Elsevier Ltd. All rights reserved.
Keywords: Video games; learning management